Поняття економічного потенціалу та концептуалізація підходів до його трактування - Лисенко, А. М.; Коряк, А. С.; Lysenko, A.; Koryak, A.; Лысенко, А. Н. (ЦНТУ, 2020)
В статті на основі дослідження підходів науковців до трактування поняття «економічний потенціал» встановлено, що розроблені підходи мають суттєві відмінності, у зв’язку з чим виникла необхідність у їх концептуалізації з виокремленням ресурсно-виробничої, ресурсно-стратегічної, виробничо-стратегічної складових та формуванням на цій основі відповідних концепцій: ресурсновиробничої, ресурсно-тратегічної, виробничо-стратегічної та ресурсно-виробничо-стратегічної. В основу формування ресурсно-виробничо-стратегічної концепції у трактуванні поняття «економічний потенціал» авторами покладено класичні підходи (виробничий, маркетинговий, ресурсний), з урахуванням чого поняття «економічний потенціал» визначено як сукупність ресурсів та можливостей, які з розвитком продуктивних сил та економічних відносин можуть бути максимально використаними у процесі вирішення стратегічних завдань. The aim of the study is to systematize scientific approaches to the interpretation of the concept of "economic potential", to prove the need for their conceptualization with the separation of resource-production, resource-strategic, production-strategic components and the formation of appropriate concepts on this basis. The article, based on a study of the approaches of scientists to the interpretation of the concept of "economic potential", found that the developed approaches have significant differences, and therefore there is a need for their conceptualization. Relevant concepts have been formed: resource-production, resource-strategic, production-strategic and resource-production-strategic. It is established that the resource-production concept provides a combination of economic resources and their optimal use with the ability to achieve maximum production. The resource-strategic concept involves the use of a set of resources in the process of solving problems for the future. Production and strategic concept involves the use of a set of elements with defined functions to ensure the production process and achieve strategic goals. The resource-production-strategic concept envisages the use of a set of economic resources and production opportunities to achieve the development goals of the business entity. It has been substantiated that the economic potential of the business entity is formed by two interrelated components: internal (resource-production, which reflects the potential of the business entity to produce goods (works, services)) and external (which characterizes the market). opportunities for the sale of such goods (works, services) to consumers and income). The formation of the resource-production-strategic concept in the interpretation of the concept of "economic potential" the authors put the classical approaches (production, marketing, resource), taking into account the concept of "economic potential" is defined as a set of resources and opportunities. relations can be used to the maximum in the process of solving strategic tasks. It is established that the prospect of further scientific developments in this direction is the study of structural components of economic potential and features of its formation and evaluation at different levels of economic systems.
The Concept of Economic Potential and Conceptualization of Approaches to Its Interpretation
Понятие экономического потенциала и концептуализация подходов к его трактовке
Keywords: економічний потенціал; ресурсно-виробнича концепція; ресурсно-стратегічна концепція; виробничо-стратегічна концепція; ресурсно-виробничо-стратегічна концепція; economic potential; resource-production concept; resource-strategic concept; production-strategic concept; resource-production-strategic concept; экономический потенциал; ресурсно-производственная концепция; ресурсно-стратегическая концепция; производственно-стратегическая концепция; ресурсно-производственно-стратегическая концепция